THE LINGUODIDACTIC ASPECT OF LEGAL TERMINOLOGY TRANSLATION PROBLEMS - LEVITAN, Konstantin (Comparative Legilinguistics, 2011)
The paper presents a linguodidactic approach to teaching legal translation based on the comparative analysis of national and cultural concept spheres, contacting in the learning process. Peculiarities of legal language and professional communication in the sphere of law, specific features of legal translation, components of legal translation competence, difficulties connected with the translation of legal terms, and strategic and methodological issues of teaching law terminology translation including phraseological units are analyzed in detail. The author describes the methods and techniques which extend the students conceptions of sociocultural context, in which the target language is used by native speakers. To provide the equivalent translation of legal texts, the students must take into consideration the specific character of national law systems, use the right translation transformations, and find relevant legal terms. The main purpose of the translation is to bring together two conceptual pictures of the world. It is supposed that such an approach can help students to learn the new ways of world conceptualization and will stimulate the self-devolopment of future translators, fostering their professional skills and creativity.